Investigations with Various Inner Shielding Distance Tests for a Novel Coupler-based CPT System Applied for Electric Vehicles Using Electromagnetic Resonant Coupling and Aluminium Shielding Material. Issue 1 (March 2020) - Duan, J; Wang, W
Abstract: Contactless power transfer (CPT) technology development has been driven rapidly over the past decade by the world-wide trends towards new energy explorations, and numerous reports have been presented in this area. This paper focuses on passive magnetic shielding, which acts as one of the major factors mainly determining the overall CPT system performance when discussing electromagnetic field flux distribution and its real-time effects on magnetic resonant coupling. As a well performance conductive metallic material, aluminium has been adopted to be a passive shielding material in the designed novel H-shape coupler CPT system in this paper, in order to evaluate and find out the optimal inner shielding distance in between the coil and the inner shielding shell. Three inner shielding distances are applied and analyzed across a critical range of system operating frequency, by which the actual CPT system performance differences from perspectives of electromagnetics and power electronics have been illustrated and compared. As a result, it can be noticed that the 15-mm inner shielding gap CPT model is able to yield an optimal system performance with a maximum system efficiency, peak system output RMS power of over 36% and 22 kW, respectively, which also shows an optimal capability to address major concerns over electric vehicle contactless charging. Besides, along with the electromagnetic field parameters generated in the model, such as actual real-time values of flux linkage, magnetic flux density and field strength, it can be found that the 15-mm inner shielding gap prototype is able to achieve better overall magnetic field performance than 5-mm and 25-mm inner shielding distance CPT models.